1996
DOI: 10.1007/bf02355033
|View full text |Cite
|
Sign up to set email alerts
|

Gastric duplication cyst: Evaluation by endoscopic ultrasonography and magnetic resonance imaging

Abstract: Endoscopic ultrasonography (EUS) and magnetic resonance imaging (MRI) are becoming popular methods for examining tumorous lesions along the upper gastrointestinal tract. Though duplication cysts are uncommon, EUS findings from gastric duplication cysts have accumulated and proven very useful for preoperative diagnosis. There have been few reports, however, concerning MRI findings from these cysts. We report herein the case of a 25-year-old man with a gastric duplication cyst. EUS demonstrated a cystic mass adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 8 publications
1
34
1
2
Order By: Relevance
“…Although upper gastrointestinal series demonstrate external pressure on the stomach, preoperative workup mainly includes abdominal ultrasonography and computed tomography scans, as well as endoscopic ultrasonography and magnetic resonance imaging [15,16] . Due to malignant transformation and the report of gastric cancer arising in duplications of the stomach [17] , surgical excision is considered to be the best treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although upper gastrointestinal series demonstrate external pressure on the stomach, preoperative workup mainly includes abdominal ultrasonography and computed tomography scans, as well as endoscopic ultrasonography and magnetic resonance imaging [15,16] . Due to malignant transformation and the report of gastric cancer arising in duplications of the stomach [17] , surgical excision is considered to be the best treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, US clearly revealed that the gastric duplication was contiguous with the gastric wall through the fourth hypoechoic layer corresponding to the muscle layer. Although endoscopic ultrasonographic findings of a gastric duplication cyst adjacent to the fourth layer of the stomach wall have been reported [17], in the present case, findings of the gastric duplication cyst adjacent to the fourth layer of the stomach wall could be clearly obtained with abdominal US. The fold-like structure of the cyst wall may be a finding specific to gastric duplication cysts.…”
Section: Discussionmentioning
confidence: 44%
“…Computed tomography often reveals a cystic mass associated with the alimentary tract. Magnetic resonance images as well as endoscopic ultrasonography are able to raise the suspicion for gastric duplication [11,12] and are popular methods of evaluating tumorous lesions along the upper GI tract. The diagnosis though is usually confirmed at laparotomy.…”
Section: Discussionmentioning
confidence: 99%